Toleransi dalam Kitab Tafsir Taisir al-Karim al-Rahman fi Tafsir al-Kalam al-Mannan - M. Thoriqul Huda; Luthfiah Luthfiah (Qolamuna : Jurnal Studi Islam, 2019)
Every religion teaches good and forbids ugliness. There is no religion that teaches the people to do evil to others until there is hostility or conflict.. Islam as a perfect religion is one of the religions blessed with the book of Samawi, and it not free from the matter of the affairs of difference between religious groups. Through the Word of God written in his book Muslims are given knowledge of attitudes in socializing with other religious people. Islam is known as a mercy for all nature. His teachings bring benefit not only to his followers but also to others. If you find an adherent who does not bring mercy then actually the religion he holds is only a formality without any appreciation. Keyword: Toleration, tafsir al-Sa’di